Cyber bullying of Indian Cricketers on internet: A study - Vinod Kumar D Chavan (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Cyberbullying has become a pervasive issue in the digital age, affecting individuals across various domains, including sports. This study delves into the phenomenon of cyberbullying targeting Indian cricketers on the internet, shedding light on its prevalence, forms, and consequences. With the proliferation of social media platforms and the increasing online presence of cricket stars, this research investigates the unique challenges faced by Indian cricketers as they navigate the virtual world. The study employs a mixed-methods approach, combining qualitative and quantitative analyses to provide a comprehensive understanding of cyberbullying against Indian cricketers. Data was collected through surveys, interviews, and content analysis of social media platforms, focusing on prominent Indian cricket players who have faced online harassment. Our findings reveal that Indian cricketers are disproportionately targeted by cyberbullies due to their high public profiles and the emotional investment of fans in cricket. Common forms of cyberbullying against cricketers include abusive comments, threats, and character assassination. Social media platforms, especially Twitter and Instagram, serve as hotspots for such vitriolic behaviour, perpetuated by anonymous trolls and disgruntled fans. The psychological impact of cyberbullying on Indian cricketers is significant, leading to stress, anxiety, and a negative impact on their performance. Many cricketers report feeling helpless and vulnerable when confronted with a barrage of online abuse. In some cases, cyberbullying has even resulted in players taking breaks from social media or seeking professional mental health support. This study also investigates the role of social media platforms and their policies in curbing cyberbullying. It identifies the need for stricter regulations and more proactive measures to protect the mental well-being of Indian cricketers and other public figures. Additionally, the study highlights the importance of media literacy and digital resilience training for athletes to empower them in dealing with cyberbullying. In conclusion, cyberbullying of Indian cricketers on the internet is a pressing issue that demands attention from stakeholders, including sports authorities, social media platforms, and society as a whole. This study provides valuable insights into the nature and impact of cyberbullying on cricketers, emphasizing the urgent need for concerted efforts to combat online harassment and protect the mental health of our sporting icons in the digital age.